Validation of an in‐vivo proton beam range check method in an anthropomorphic pelvic phantom using dose measurements. Issue 4 (26th March 2015) - Bentefour, El H.; Tang, Shikui; Cascio, Ethan W.; Testa, Mauro; Samuel, Deepak; Prieels, Damien; Gottschalk, Bernard; Lu, Hsiao‐Ming
Abstract : Purpose: In‐vivo dosimetry and beam range verification in proton therapy could play significant role in proton treatment validation and improvements. In‐vivo beam range verification, in particular, could enable new treatment techniques one of which could be the use of anterior fields for prostate treatment instead of opposed lateral fields as in current practice. This paper reports validation study of an in‐vivo range verification method which can reduce the range uncertainty to submillimeter levels and potentially allow for in‐vivo dosimetry. Methods: An anthropomorphic pelvic phantom is used to validate the clinical potential of the time‐resolved dose method for range verification in the case of prostrate treatment using range modulated anterior proton beams. The method uses a 3 × 4 matrix of 1 mm diodes mounted in water balloon which are read by an ADC system at 100 kHz. The method is first validated against beam range measurements by dose extinction measurements. The validation is first completed in water phantom and then in pelvic phantom for both open field and treatment field configurations. Later, the beam range results are compared with the water equivalent path length (WEPL) values computed from the treatment planning system XIO. Results: Beam range measurements from both time‐resolved dose method and the dose extinction method agree with submillimeter precision in water phantom. For the pelvic phantom, when discarding two of the diodes that show sign of significant range mixing, the two methods agree with ±1 mm. Only a dose of 7 mGy is sufficient to achieve this result. The comparison to the computed WEPL by the treatment planning system (XIO) shows that XIO underestimates the protons beam range. Quantifying the exact XIO range underestimation depends on the strategy used to evaluate the WEPL results. To our best evaluation, XIO underestimates the treatment beam range between a minimum of 1.7% and maximum of 4.1%. Conclusions: Time‐resolved dose measurement method satisfies the two basic requirements, WEPL accuracy and minimum dose, necessary for clinical use, thus, its potential for in‐vivo protons range verification. Further development is needed, namely, devising a workflow that takes into account the limits imposed by proton range mixing and the susceptibility of the comparison of measured and expected WEPLs to errors on the detector positions. The methods may also be used for in‐vivo dosimetry and could benefit various proton therapy treatments.